If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (fx) = 2x + -6 fx = 2x + -6 Reorder the terms: fx = -6 + 2x Solving fx = -6 + 2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -6x-1 + 2 Simplifying f = -6x-1 + 2 Reorder the terms: f = 2 + -6x-1
| f(x)=x^2-10x+8 | | 25-64z^2=0 | | 20q-4q+q-15q=18 | | 420=16x*16x+27x | | 6(7x-3)-6(4-3x)= | | -3y+2+2y-5= | | 6n=30+3[n-4]forn | | 5(3x+6)+3(7x+6)= | | g(x)=27-3x | | 5z=1.7+3.8 | | lne^21/3 | | 22+e^3x=30 | | 20r-17r=15 | | -5(x+7)-43=3-56 | | 8=3.2h | | F(7)=-2x-1 | | 2y+x+3x-4= | | 11w-10w=8 | | 2x-22+x+4=360 | | 5w-9w=28 | | 2x11/2 | | 24x+8-26x=6-8 | | 8x+7y=500 | | 6=4+2j | | -26=-8y+6(y-5) | | 13c-9c=16 | | -23-38= | | -7x-2x-11=-13 | | 10x+5+6x+5=90 | | z=y^2-x^2 | | 13-42=3(x-1)-5 | | f(x)=3-11 |